Enhancement the Knowledge and Skills of SMK N 6 Kendal Students Through the Practice of Making Kombucha Tea: Peningkatan Pengetahuan dan Keterampilan Siswa SMK N 6 Kendal Melalui Praktik Pembuatan Teh Kombucha - Rachma, Anisa; Rohadi, Rohadi; Kunarto, Bambang (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2025)
The biotechnology subject for processing agricultural products at SMK N 6 Kendal is considered lacking. In fact, skills in the field of biotechnology can be applied to food production and this is in accordance with the competencies required by students majoring in Agribusiness on Agricultural Product Processing (APHP) at SMK N 6 Kendal. The aim of community service activities (PKM) is to increase students' knowledge and skills in making Kombucha tea. The PKM method includes several stages, namely, survey, coordination of preparation, implementation, monitoring and evaluation. The stages of PKM implementation are delivered through lectures and practice. The PKM results show that the average score of the questionnaire test results with both the pretest and post-test questionnaires is very good, with an average score of 16.2 (pretest) and 16.3 (post-test) out of a potential questionnaire score of 20. However Thus, lectures are not effective for the purpose of increasing student knowledge.